Introduction to child development - Dworetzky, John. (Minneapolis/St. Paul : West Pub. Co., 1993)
A text covering the GCSE Psychology: Child Development syllabus and certain areas of BTEC Nursing and Caring and BTEC Social Sciences, which discusses the main theories of child development, the ways in which psychologists investigate and apply their knowledge and which encourages students to evaluate the methods and use some of the techniques in their own project work. The layout of the book is intended to make it suitable for different styles of teaching. The core text includes review boxes with summaries of key ideas for revision, background reading, and extra notes in the margin containing definitions, comments and open-ended questions and exercises.
Includes bibliographical references and index.
Keywords: Child development; Child psychology